Mental Health Problems during COVID-19 Pandemic - Achmad Yasin Mustamin; Yanasta Yudo Pratama; Tri Ani Marwati (Universitas Ahmad Dahlan, 2022)
Mental health is essential to achieving a comprehensive degree of health, but it has not become a top priority in some developing countries. The COVID-19 pandemic has made it difficult for people to access physical and mental health services. The situation of this pandemic pushes WHO and mental health services as an integral component of the condition. Only a third of healthcare providers in the United States can receive standardized mental health care. In developing countries with low and middle incomes, 75% more people experience neurological disorders, mental disorders, and addictive substance abuse. The prevalence of patients affected by Post-Traumatic Stress Disorder (PTSD) is around 4-41%, and the prevalence of major depression due to the epidemic - increased by 7%. Unfortunately, of those with mental disorders, only a tiny percentage get proper treatment.